Pengaruh Good Governance terhadap Kinerja Karyawan di Badan Perencanaan Penelitian dan Pengembangan Kabupaten Karimun - Adelya Rifdah; Bachruddin Saleh Luterlean (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Good governance is a principle that can treat political bureaucracy, which is considered to be frequently found in cases of corruption, bribery and abuse of power, including various violations of human rights. The Planning, Research and Development Agency of Karimun Regency through the implementation of E-Planning since 2017, shows that it has implemented Good Governance. In this case, all employees of the Karimun Regency Planning, Research and Development Agency participate in implementing good governance because they carry out government tasks. This study aims to identify the magnitude of the influence of Good Governance on Employee Performance in the Planning, Research and Development Agency of Karimun Regency. This research uses descriptive and causal research using quantitative research methods. This study uses a non-probability sampling technique, with the sample used is a saturated sample. Where the samples in this study are all employees in the Planning, Research and Development Agency of Karimun Regency, amounting to 65 respondents. The results of descriptive analysis show that the value obtained is 77.79%, so that Good Governance is in the good category and the employee's performance is in the good category with the value obtained of 77.98%. The effect of good governance on the performance of the employees of the Planning, Research and Development Agency of Karimun Regency is 47.3%, while the remaining 52.7% is the contribution of other variables not examined in this study.